A Scoping Review and Conceptual Framework Examining the Role of Sleep Disturbance in Financial Exploitation in Older Adults. (July 2022) - Armendariz, Jessica R.; Han, S. Duke; Fung, Constance H.
Sleep disturbances and financial exploitation have both been linked to impaired cognitive ability, loneliness, and depressed mood in older adults, suggesting a potential role of sleep disturbances in increasing vulnerability to financial exploitation. We sought to identify evidence linking sleep disturbances to financial exploitation. We conducted a systematic search of MEDLINE, PubMed Central, and National Center for Biotechnology Information Bookshelf for relevant published articles on sleep and financial exploitation. Three studies examining both sleep and financial exploitation were identified. None of the studies explored sleep disturbances as a cause of financial exploitation. More work needs to be done to examine the role of sleep disturbances in financial exploitation. We propose a conceptual framework for identifying possible associations among sleep disturbance, biopsychosocial, and decision-related situational factors to guide further exploration of relationships between sleep and financial exploitation.